The Influence of Cause Related Marketing Towards Purchase Intention in Local Fashion Brands Indonesia - Maharani Feminingtyas , Arum; Mayangsari, Lidia (KnE Social Sciences, 2020)
Cause-Related Marketing (CRM) becomes an increasingly popular nowadays as a used tool by companies operating in the market. CRM campaign represents form of a partnership in a creative manner which companies, nonprofit organization, and customers makes charities for collective benefits and believed as the most effective marketing strategy for company rather than other strategies, as customers have shifting paradigms in perception and recognition towards products that they are increasingly looking for products or brand that also have positive shared value in the surroundings or called the societal marketing concept. CRM used by brand marketers who believes that this approach significantly helps to improve the purchase intention. Knowing that, researcher want to get more inclusive and realistic understanding about it. The purpose of this research study is to analyze the influence of CRM towards purchase intention in local fashion brands Indonesia. Using simple regression analysis, the researcher will gather data from about 150-400 samples using purposive sampling method by spreading questionnaire via online. Keywords: Cause Related Marketing; Purchase Intention, Local Fashion Brands